In situ high temperature atomic level dynamics of large inversion domain formations in monolayer MoS2 - Chen, J; Zhou, S; Wen, Y; Ryu, G; Allen, C; Lu, Y; Kirkland, A; Warner, J (Royal Society of Chemistry, 2019)
Here we study the high-temperature formation and dynamics of large inversion domains (IDs) that form in monolayer MoS2 using atomic-resolution annular dark-field scanning transmission electron microscopy (ADF-STEM) with an in situ heating stage. We use temperatures above 700 °C to thermally activate rapid S vacancy migration and this leads to a formation mechanism of IDs that differs from the one at room temperature, where S vacancy migration is limited. We show that at high temperatures the formation of IDs occurs from intersected networks of long S vacancy line defects, whose strain fields are non-orthogonal and trigger large scale atomic reconstructions. Once formed, the IDs are influenced by the dynamic behaviour of nearby line defects and voids. With Mo and S atoms undergoing movement, the two types of ID grain boundaries can shift to allow further expansion of the ID area along the adjoining line defects. We reveal that IDs serve as metastable configurations between line defect rearrangements and eventual void formation under electron beam irradiation during heating. The formation of voids near to the IDs causes them to revert back to pristine lattice, which has the effect of restricting the ID domain size to a certain range (e.g. 3–5 nm in our observation) instead of continuously enlarging. This study provides insights into how the MoS2 IDs form and evolve at high temperature and can benefit the tailoring of electronic properties of two dimensional materials by structural manipulation.